Produção de alface em garrafas pet - Teixeira, Sebastião Luiz; Fonseca , Joaquim Carlos da; Bortolotto, Rosane Aparecida; Carraro, Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf